2017
DOI: 10.1039/c7ra07799h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous degradation of tetracycline by a microbial fuel cell and its toxicity evaluation by zebrafish

Abstract: Tetracycline (TC) is the second most commonly used antibiotic despite its high toxicity and persistence. In this study, a new approach for the anaerobic biodegradation of TC in a microbial fuel cell (MFC), with glucose-TC mixtures as the substrate, under gradient acclimation conditions was explored. Within 7 days, approximately 79.1% of TC was degraded by the MFC. This value was higher than that obtained through a traditional anaerobic method (14.9%). The TC degradation rates in MFCs with a closed circuit were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In these cells, exoelectrogenic bacteria directly converted chemical energy stored in organic waste into electrical energy. [1][2][3] Despite their obvious benets, however, MFCs suffered from low energy production and poor organic degradation. Thus, the performance of MFCs should be improved for practical application, which was inuenced by several factors, including microbial species, types and properties of the substrate, diaphragm material, electrode material, and system design.…”
Section: Introductionmentioning
confidence: 99%
“…In these cells, exoelectrogenic bacteria directly converted chemical energy stored in organic waste into electrical energy. [1][2][3] Despite their obvious benets, however, MFCs suffered from low energy production and poor organic degradation. Thus, the performance of MFCs should be improved for practical application, which was inuenced by several factors, including microbial species, types and properties of the substrate, diaphragm material, electrode material, and system design.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that tetracycline is difficult to biodegrade, whereas sulphonamides have been found to be easily assimilated as a carbon or nitrogen source for microbial growth [27, 28]. However, Wang et al [29] stressed the essentiality of the gradual domestication of micro-organisms during the process of tetracycline removal by MFCs, and 79% of tetracycline was removed within 7 days in closed MFCs after a domestication cycle of 5 weeks. Here, no inoculation and acclimation resulted in a relatively slow tetracycline degradation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the degradation of antibiotics was particularly faster under the CC. 24 Toxicity evaluation of zebrash embryos…”
Section: Degradation Of Otc and Ctcmentioning
confidence: 99%
“…16 The MFC can convert energy and produce electricity while degrading organic matter, 17,18 such as easily degradable 19,20 and bio-refractory organics. 21,22 Several studies have recently focused on the degradation of TCs by MFC 23,24 to improve TC removal. However, the characterization and degradation mechanisms of the different kinds of TCs by MFC remain unknown.…”
Section: Introductionmentioning
confidence: 99%